Penerapan Tehnik Sablon Gradiasi pada Media Material Berbasis Digital Printing : Literatur Review - Mesah Nur Sejati (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Background: Screen printing is one of the printing techniques that is quite developed in society. Digital printing is an activity of printing images using sophisticated machines in the form of printers. The purpose of this study is to determine the application of gradient screen printing techniques on media materials based on digital printing from the design of a literature review. Method: This research method is with a literature review design. Source: four scientific databases used to obtain relevant sources based on the problems of applying gradient screen printing techniques to media materials based on printing technology. Search: The search was conducted on publications between 2019 and 2024 with the keyword gradient screen printing. Study selection: A search of research journals on ProQuest, IEEE Xplore, Emerald insight, Google Scholars found a total of 96,229 data results. After that, the results were classified again into 6,407 journal sources. After that, it was classified in the last 5 years, namely 2019 to 2024, which was 3,656 results. After a special reclarification on the application of gradient screen printing techniques on media materials based on printing technology, 6 data were obtained. Data analysis: The results of the research discussed used a special conceptual approach that analyzed a framework to achieve goals using the PRISMA method. Conclusion: Based on various research articles discussed, it can be concluded that the application of gradient screen printing techniques on media materials based on printing technology is one of the screen printing techniques that is quite popular, especially in the world of modern clothing design today. Gradient screen printing based on printing technology is a technique for printing designs on fabrics with a blend of colors that flow (gradation) from one color to another smoothly.